PEMANFAATAN ROTAN NON KOMERSIAL SEBAGAI BAHAN BAKU MEBEL DITINJAU DARI SIFAT FISIS DAN MEKANIS - Effendi Arsad; Suroto Suroto (Jurnal Riset Industri Hasil Hutan, 2011)
Rattan in good quality is curently difficult to obtain and it price is quite expensive.  So, it is needed to utilize non commercial rattan as substitute  material.  By identification of basic characteristics , such as phisical, mechanical, chemical and anatomy structure, every species of non commercial rattan can be used appropriately.   The objectives of this research is to optimize utilization  non commercial rattan as subtitute material and develop rattan manufacturing industry especially by identivication of the physical and mechanical characteristics.  Five (5) rattan species studied here are marau (Calamus mettanensis Becc), toho (Calamus spp), galang (Daemonorops verticilaris Griff Mart), hijau (Calamus spp. and simpurut (Calamus panajuga Becc) whic derived  from central Kalimantan.  The research result based on physical characteristic rang for diameter is between  6,2 – 27,2 mm, inter-segment length 10 – 28 cm, moisture content 12,50 – 16,48 % and density 1,03 – 1,61 gr/cm3.  While mechanical characteristics range for modulus of elasticity is between 364,03 – 1934,29 kg/cm2, compression strenth 127,55 – 441,04 kg/cm2 and  tensile strength 197,34 – 394,20 kg/cm2.  Those rattan species can be optimized as craft industry raw material especialy for furniture and rattan  matting.Keywords: rattans, physical, mechanical, craft.